How do Chinese firms adjust their financial leverage: An empirical investigation using multiple GMM models - Ajid ur Rehman; Man Wang; Sultan Sikandar Mirza (China Finance and Economic Review, 2017)
Background: Given the unique market setting and institutional environment of China, this study tries to investigate targeting behavior of Chinese firms towards leverage and the determinants of leverage policy in China at various levels. Methods: For this purpose, we used an extensive set of data of 760 firms over a period from 2001 to 2013. To investigate the adjustment behavior towards target leverage policy, this study uses the GMM (generalized method of moments) models of Arellano and Bover (J Econ 68:29-51, 1995)/Blundell and Bond (Econ Rev 19:321-340, 2000) to estimate the adjustment behavior and adjustment speed towards a target level of leverage. The study finds that Chinese firms have a target level of leverage and firms tries to adjust to their target. Results: We found that adjustment rate of Chinese state-owned enterprises is higher than Chinese non-state owned, indicating an aggressive leverage policy for SOEs (state-owned enterprises). Further, the study found that some firm-level factors like firm size and growth opportunities have significant and positive effect on firms leverage. Profitability and firm liquidity is found to have a negative relationship with firm leverage. At country level, GDP (gross domestic product) is found to have positive impact of firm leverage policy. The negative relationship of lending rate with leverage shows that firms in China reduce debt financing when lending rates in the market increase. Conclusions: All these findings indicate significant policy implications for Chinese firms. At adjustment level, regulatory bodies should ensure that all firms are at ease while raising their debt and thus avoid a pecking order in lending policy. At industry level, institutions should try to curtail industry concentration to provide an equal ground of debt issuing to the firms.
Keywords: 330; Target leverage; Multilevel determinants; GMM; Chinese firms